Carnival at candlelight (Magic tree house. Merlin missions, 5, 1, 2006)
While on a mission to prove to Merlin that they can use magic wisely, Jack and Annie travel to seventeenth-century Venice, Italy, to save the city from disaster.
Book of magic , Carnival , Grand lady of the lagoon , Rats! , Lorenzo , Disaster , King and the ruler , Home by day , Painting.

Portrait of an unknown woman (Gabriel Allon novels, 22, 1, 2022)
"A gripping story of deception in the world of international fine art. Restorer and spy Gabriel Allon embarks on a dangerous hunt across Europe for the secret behind the forgery of a seventeenth-century masterpiece that has fooled experts and exchanged hands for millions"--
Daniel Silva.

The waters of eternal youth: a Commissario Guido Brunetti mystery (Guido Brunetti mysteries, 25, 1, 2016)
Hired to investigate a suspicious near-drowning that left a girl permanently brain damaged years earlier, Brunetti struggles to determine if a crime was actually committed in a case set against a backdrop of dynamic transitions in contemporary Venice.

Falling in love (Guido Brunetti mysteries, 24, 1, 2015)
Attending a performance by an opera star he saved in Death at La Fenice, Brunetti learns that the singer is being stalked by an obsessed fan who subsequently attacks a fellow performer.

Unto us a son is given (Guido Brunetti mysteries, 28, 1, 2019)
"Your situation is always ambiguous, isn't it, Guido?", his father-in-law, Count Orazio Falier, observes of Donna Leon's soulful detective, Guido Brunetti, at the beginning of her superb 28th Brunetti novel, Unto Us A Son Is Given . "The world we live in makes that necessary," Brunetti presciently replies. Count Falier was urging his Venetian son-in-law to investigate, and preferably intervene in, the seemingly innocent plan of the Count's best friend, the elderly Gonzalo Rodr©Ưguez de Tejada, to adopt a much younger man as his son. Under Italian inheritance laws this man would then be heir to Gonzalo's entire fortune, a prospect Gonzalo's friends find appalling. For his part, Brunetti wonders why the old man, a close family friend, can't be allowed his pleasure in peace. And yet, what seems innocent on the Venetian surface can cause tsunamis beneath. Gonzalo unexpectedly, and literally, drops dead on the street, and one of his friends just arrived in Venice for the memorial service, is strangled in her hotel room--having earlier sent Gonzalo an email saying "We are the only ones who know you cannot do this," referring to the adoption. Now with an urgent case to solve, Brunetti reluctantly untangles the long-hidden mystery in Gonzalo's life that ultimately led to murder--a resolution that brings him way more pain than satisfaction. Once again, Donna Leon brilliantly plumbs the twists and turns of the human condition, reuniting us with some of crime fiction's most memorable and enduring characters.-- Count Orazio Falier urges his son-in-law, detective Guido Brunetti, to investigate the seemingly innocent plan of the Count's best friend, the elderly Gonzalo Rodr©Ưguez de Tejada, to adopt a much younger man as his son. Under Italian inheritance laws this man would then be heir to Gonzalo's entire fortune, a prospect Gonzalo's friends find appalling. Brunetti wonders why the old man can't be allowed his pleasure in peace. Then Gonzalo dies unexpectedly, and a friend in Venice for the memorial service is strangled in her hotel room after protesting the adoption. -- adapted from publisher's info

Palazzo: a novel (Recorded Books, Inc., Delacorte Press, Random House Large Print, Blackstone Publishing, Random House Publishing Group, 2023)
A captivating new novel from Danielle Steel, whose countless #1 New York Times bestselling novels have made her one of America's favorite storytellers. After her parents perish in a tragic accident, Cosima Saverio assumes leadership of her family's haute couture Italian leather brand. While navigating the challenges of running a company at twenty-three, Cosima must also maintain the four-hundred-year-old family palazzo in Venice and care for her younger siblings: Allegra, who survived the tragedy that killed their parents with scars and a spinal injury, and Luca, who has a penchant for wild parties, pretty women, and poker tables. Cosima navigates her personal and professional challenges with a wisdom beyond her years, but her success has come at a cost: Her needs are always secondary. She's married to the business, and her free time is given to those who rely on her . . . until she meets Olivier Bayard, the founder of France's most successful ready-to-wear handbag company. A brief conversation on her palazzo's terrace turns into a tour of the Saverio workshop, and, fifteen years after her parents' deaths, Cosima has found a confidant. Now the business is financially stable and generating enough income for the Saverios to live comfortably. Then Luca loses a hefty sum at the casino, and his debt must be repaid with money or his life. Cosima, forced to bail him out, is given an impossible choice: List the palazzo, sell a third of the family business, or let Luca fend for himself. But is there another way to save everything she has fought for before it goes up in flames? In Palazzo, Danielle Steel delivers a striking tale of family roots, ruin, and renewal.
Danielle Steel.

Earthly remains (Guido Brunetti mysteries, 26, 1, 2017)
"Donna Leon's bestselling mystery novels have won a multitude of fans for their insider's portrayal of Venice. From family meals to vaporetti rides, the details and rhythms of everyday life are an integral part of this beloved series. But so are the never-ending influx of tourists and the suffocating corruption. Through it all, Leon's Commissario Guido Brunetti, a good man who loves his family and his city, has been an enduring figure, but in Earthly Remains, Brunetti's endurance is tested more than ever before. During an interrogation, Brunetti acts rashly, doing something he quickly comes to regret, and in the fallout, he realizes that he needs a break. Granted leave from the Questura, Brunetti's wife Paola ships him off to a villa owned by a wealthy relative on Sant'Erasmo, one of the largest islands in the laguna. There he intends to pass his days rowing, and his nights reading Pliny's Natural History. The recuperative stay goes according to plan until David Casati, the caretaker of the house, goes missing following a sudden storm. Now, Brunetti feels compelled to investigate, to set aside his leave of absence and understand what happened to the man who had become his friend"--

Playing with fire: a novel (Brilliance Audio on compact disc, ,, 2016)
In a shadowy antiques shop in Rome, violinist Julia Ansdell happens upon a curious piece of music--the Incendio waltz--and is immediately entranced by its unusual composition. Full of passion, torment, and chilling beauty, and seemingly unknown to the world, the waltz, its mournful minor key, its feverish arpeggios, appear to dance with a strange life of their own. Julia is determined to master the complex work and make its melody heard. Back home in Boston, from the moment Julia's bow moves across the strings, drawing the waltz's fiery notes into the air, something strange is stirred--and Julia's world comes under threat. The music has a terrifying and inexplicable effect on her young daughter, who seems violently transformed. Convinced that the hypnotic strains of Incendio are weaving a malevolent spell, Julia sets out to discover the man and the meaning behind the score. Her quest beckons Julia to the ancient city of Venice, where she uncovers a dark, decades-old secret involving a dangerously powerful family that will stop at nothing to keep Julia from bringing the truth to light.

Death in Venice (Dover Publications, Harper Collins Publishers, HarperCollins, Ecco, Murine Publications LLC, Otbebookpublishing, Neeland Media LLC, 2009)
A new translation of the Nobel laureate's famous classic follows the story of successful aging writer Gustave von Aschenbach, whose search for spiritual fulfillment in Venice leads to erotic ruin when he becomes obsessed with an alluring Polish youth, Tadzio.

Give unto others (Guido Brunetti mysteries, 31, 1, 2022)
"What role can or should loyalty play in the life of a police inspector? It's a question Commissario Guido Brunetti must face and ultimately answer in Give unto Others, Donna Leon's splendid thirty-first installment of her acclaimed Venetian crime series. Brunetti is approached for a favor by Elisabetta Foscarini, a woman he knows casually, but her mother was good to Brunetti's mother, so he feels obliged to at least look into the matter privately, and not as official police business. Foscarini's son-in-law, Enrico Fenzo, has alarmed his wife (her daughter) by confessing their family might be in danger because of something he's involved with. Since Fenzo is an accountant, Brunetti logically suspects the cause of danger is related to the finances of a client. Yet his clients seem benign: an optician, a restaurateur, a charity established by his father-in-law. However, when his friend's daughter's place of work is vandalized, Brunetti asks his own favors--that his colleagues Claudia Griffoni, Lorenzo Vianello, and Signorina Elettra Zorzi assist his private investigation, which soon enough turns official as they uncover the dark and Janus-faced nature of a venerable Italian institution. Exploring the wobbly line between the criminal and non-criminal, revealing previously untold elements of Brunetti's past, Give unto Others shows that the price of reciprocity can be steep"-- Provided by publisher.

Trace elements (Guido Brunetti mysteries, 29, 1, 2020)
"When Dottoressa Donato calls the Questura to report that a dying patient at the hospice Fatebenefratelli wants to speak to the police, Commissario Guido Brunetti and his colleague, Claudia Griffoni, waste no time in responding. "They killed him. It was bad money. I told him no," Benedetta Toso gasps the words about her recently deceased husband, Vittorio Fadalto. Even though he is not sure she can hear him, Brunetti softly promises he and Griffoni will look into what initially appears to be a private family tragedy. They discover that Fadalto worked in the field collecting samples of contamination for a company that measures the cleanliness of Venice's water supply and that he had died in a mysterious motorcycle accident. Distracted briefly by Vice Questore Patta's obsession with youth crime in Venice, Brunetti is bolstered once more by the remarkable research skills of Patta's secretary, Signora Elettra Zorzi. Piecing together the tangled threads, in time Brunetti comes to realize the perilous meaning in the woman's accusation and the threat it reveals to the health of the entire region. But justice in this case proves to be ambiguous, as Brunetti is reminded it can be when, seeking solace, he reads Aeschylus's classic play The Eumenides"--

So shall you reap (Guido Brunetti mysteries, 32, 1, 2023)
"In the thirty-second installment of Donna Leon's bestselling series, a connection to Guido Brunetti's own youthful past helps solve a mysterious murder. On a cold November evening, Guido Brunetti and Paola are up late when a call from his colleague Ispettore Vianello arrives, alerting the Commissario that a hand has been seen in one of Venice's canals. The body is soon found, and Brunetti is assigned to investigate the murder of an undocumented Sri Lankan immigrant. Because no official record of the man's presence in Venice exists, Brunetti is forced to use the city's far richer sources of information: gossip and the memories of people who knew the victim. Curiously, he had been living in a small house on the grounds of a palazzo owned by a university professor, in which Brunetti discovers books revealing the victim's interest in Buddhism, the revolutionary Tamil Tigers, and the last crop of Italian political terrorists, active in the 1980s. As the investigation expands, Brunetti, Vianello, Commissario Griffoni, and Signora Elettra each assemble pieces of a puzzle-random information about real estate and land use, books, university friendships-that appear to have little in common, until Brunetti stumbles over something that transports him back to his own student days, causing him to reflect on lost ideals and the errors of youth, on Italian politics and history, and on the accidents that sometimes lead to revelation"--

Othello (Timeless Shakespeare, ,, 2012)
Unique features include an extensive overview of Shakespeare's life, world, and theater by the general editor of Signet Classic Shakespeare series, plus a special introduction to the play by the editor Sylvan Barnet, Tufts University. This book contains information on the source from which Shakespeare derived "Othello"--selections from Giraldi Cinthio's "Hecatommithi". Special introduction by Alvin Kernan, Princeton University.

Olivia goes to Venice (Olivia books (Ian Falconer), 6, 1, 2010)
On a family vacation in Venice, Olivia indulges in gelato, rides in a gondola, and finds the perfect souvenir.

Transient desires (Guido Brunetti mysteries, 30, 1, 2021)
In his many years as a commissario, Guido Brunetti has seen all manner of crime and known intuitively how to navigate the various pathways in his native city, Venice, to discover the person responsible. Now, in Transient Desires, the thirtieth novel in Donna Leon's masterful series, he faces a heinous crime committed outside his jurisdiction. He is drawn in innocently enough: two young American women have been badly injured in a boating accident, joy riding in the Laguna with two young Italians. However, Brunetti's curiosity is aroused by the behavior of the young men, who abandoned the victims after taking them to the hospital. If the injuries were the result of an accident, why did they want to avoid association with it? As Brunetti and his colleague, Claudia Griffoni, investigate the incident, they discover that one of the young men works for a man rumored to be involved in more sinister nighttime activities in the Laguna. To get to the bottom of what proves to be a gut-wrenching case, Brunetti needs to enlist the help of both the Carabinieri and the Guardia di Costiera. Determining how much trust he and Griffoni can put in these unfamiliar colleagues adds to the difficulty of solving a peculiarly horrible crime whose perpetrators are technologically brilliant and ruthlessly organized.

The wings of the dove (A Norton critical edition, ,, 2009)
Originally published in 1902, this is a story of deceit and betrayal, as well as of forgiveness. Milly Theale is an heiress with a short time to live and a passion for experiencing life to its fullest. Merton Densher is the man she loves, and the magnificent, predatory Kate Croy is the woman he loves, and will conspire with against Millie.

Drawing conclusions (Guido Brunetti mysteries, 20, 1, 2012)
Nearly twenty years ago, when a conductor was poisoned and the Questura sent a man to investigate, readers first met Commissario Guido Brunetti. Since 1992's Death at La Fenice, Donna Leon and her shrewd, sophisticated, and compassionate investigator have been delighting readers around the world. For her millions of fans, Leon's novels have opened a window into the private Venice of her citizens, a world of incomparable beauty, family intimacy, shocking crime, and insidious corruption. This internationally acclaimed, bestselling series is widely considered one of the best ever written, and Atlantic Monthly Press is thrilled to be publishing the twentieth installment, Drawing Conclusions, this spring.Late one night, Brunetti is called away from dinner to investigate the death of a widow in her modest apartment. Though there are some signs of a struggle, the medical examiner rules that she died of a heart attack. It seems there is nothing for Brunetti to investigate. But he can't shake the feeling that something or someone may have triggered her heart attack, that perhaps the woman was threatened. Conversations with the woman's son, her upstairs neighbor, and the nun in charge of the old-age home where she volunteered, do little to satisfy Brunetti's nagging curiosity. With the help of Inspector Vianello and the ever-resourceful Signorina Elettra, perhaps Brunetti can get to the truth and find some measure of justice.Insightful and emotionally powerful, Drawing Conclusions reaffirms Donna Leon's status as one of the masters of literary crime fiction.

The collector: a novel (Gabriel Allon novels, 23, 1, 2023)
Legendary art restorer and spy Gabriel Allon joins forces with a brilliant and beautiful master-thief to track down the world's most valuable missing painting but soon finds himself in a desperate race to prevent an unthinkable conflict between Russia and the West.

The Thief Lord (Listening Library, Random House Audio Pub. Group, Scholastic, Random House, 2002)
Two brothers, having run away from the aunt who plans to adopt the younger one, are sought by a detective hired by their aunt, but they have found shelter with--and protection from--Venice's "Thief Lord." Welcome to the magical world of Venice, Italy, where hidden canals and crumbling rooftops shelter runaways and children with incredible secrets.

By its cover: a Commissario Guido Brunetti mystery (Guido Brunetti mysteries, 23, 1, 2014)
One afternoon, Commissario Guido Brunetti gets a frantic call from the director of a prestigious Venetian library. Someone has stolen pages out of several rare books. After a round of questioning, the case seems clear: the culprit must be the man who requested the volumes, an American professor from a Kansas university. The only problem--the man fled the library earlier that day, and after checking his credentials, the American professor doesn't exist. As the investigation proceeds, the suspects multiply. And when a seemingly harmless theologian, who had spent years reading at the library turns up brutally murdered, Brunetti must question his expectations about what makes a man innocent, or guilty.